2012
DOI: 10.1111/j.1542-4774.2012.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Has Democratization Reduced Infant Mortality in Sub-Saharan Africa? Evidence From Micro Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
146
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(152 citation statements)
references
References 73 publications
(104 reference statements)
6
146
0
Order By: Relevance
“…Over the last two decades, numerous studies have linked democracies to higher social welfare provisions than authoritarian regimes (Alesina, Baqir, & Easterly, ; Haggard & Kaufman, ; Lake & Baum, ; McGuire & Olson, ; Olson, ; but see Adolf, ). Democracies also appear to fare better than most authoritarian systems on health outcomes such as infant mortality and life expectancy (Besley & Kudamatsu, ; Gerring, Thacker, & Alfaro, ; Kudamatsu, ; McGuire, ; Navia & Zweifel, ). Yet when comparing the world's two most populous nations, public health is unambiguously worse in India than in China (Dummer & Cook, ; Ma & Sood, ).…”
mentioning
confidence: 99%
“…Over the last two decades, numerous studies have linked democracies to higher social welfare provisions than authoritarian regimes (Alesina, Baqir, & Easterly, ; Haggard & Kaufman, ; Lake & Baum, ; McGuire & Olson, ; Olson, ; but see Adolf, ). Democracies also appear to fare better than most authoritarian systems on health outcomes such as infant mortality and life expectancy (Besley & Kudamatsu, ; Gerring, Thacker, & Alfaro, ; Kudamatsu, ; McGuire, ; Navia & Zweifel, ). Yet when comparing the world's two most populous nations, public health is unambiguously worse in India than in China (Dummer & Cook, ; Ma & Sood, ).…”
mentioning
confidence: 99%
“…Empirical research has already found evidence supporting the hypothesis that democratisation improves human development in regions such as Latin America (Brown & Hunter 1999) and Africa (Kudamatsu 2012). Our goal is to assess if this relationship also holds among East Central European and former Soviet countries.…”
Section: Democratisation and Human Development In Post-communist Counmentioning
confidence: 95%
“…20). Indeed, a number of studies have shown that in countries with better institutions, citizens enjoy higher life expectancy (Besley & Kudamatsu, 2006;Kudamatsu, 2012) and report higher levels of self-rated health (Krueger, Dovel, & Denney, 2015), whereas the government tends to prioritize health spending (Kazemi Karyani, Homaie Rad, Pourreza, & Shaahmadi, 2015).…”
Section: Introductionmentioning
confidence: 99%